An Empirical Analysis of the Working Capital Management Practices of South African Retail Firms - Sibindi, Athenia; Mandipa, Garikai (Acta Universitatis Danubius. Œconomica, 2022)
Working capital is considered to be the ‘lifeblood’ of businesses. Working capital strategy can best be described as a strategy made by the firm for making decisions on two important things, which are how much to invest in each component of current assets and how to finance those investments. Against this backdrop the present inquiry sought to examine the working capital management strategies employed by the South African retail firms. The study employed a panel of retail firms listed on the Johannesburg Stock Exchange (JSE) for the period 2010-2019 as the unit of analysis. Working capital management were proxied by cash conversion cycle (CCC), average age of in-ventory (AAI), average collection period (ACP), and average payment period (APP). Descriptive and correlational analyses was employed for empirical investigation. The data was derived from the Orbis dataset and taken from the financial statements of 16 retail companies listed on the JSE. The findings of the study revealed that South African retail firms predominantly employed the con-servative working capital policies. More specifically, the results of the study documented that ACP and AAI were higher than APP for the sample of South African retail firms. Thus, the firms were holding more current assets in the form of trade receivables and inventories relative to current liabilities which in turn increases the length of CCC.